Promoting Health-Related Cardiorespiratory Fitness in Physical Education: The Role of Lesson Context and Teacher Behavior in an Observational Longitudinal Study - De Moraes-Ferrari, G (Human Kinetics Publishers Inc., 2023)
Purpose: Physical education (PE) is an important context for promoting health-related cardiorespiratory fitness (CRF) in youth. Within PE, the lesson context and teacher behavior may be relevant for the promotion CRF; however, evidence is scarce. Therefore, the purpose of this study was to assess whether students’ CRF improvement in a school year was explained by PE lesson context and teacher behavior. Method: A 1-year observational one-group pretest/posttest study, including 212 students, was conducted. The Progressive Aerobic Cardiovascular Endurance Run (PACER) was used to assess CRF. The PE lesson context and teacher behavior were assessed using the System for Observing Fitness Instruction Time. Multivariate linear regression models were performed to examine the effect of time spent in each category of lesson content and teacher behavior on the change in PACER laps from the beginning to the end of the school year. Results: Lesson time spent in gameplay (boys: B = −0.24, 95% confidence interval [CI] [−0.45, −0.02]; girls: B = −0.17, 95% CI [−0.29, −0.04]), time spent by teachers in instruction tasks (boys: B = 0.38, 95% CI [0.17, 0.60]; girls: B = 0.33, 95% CI [0.17, 0.48]), and promoting fitness (girls: B = 1.40, 95% CI [0.60, 2.20]) were associated to PACER improvement. Lesson time spent in general content (boys: B = −0.24, 95% CI [−0.45, −0.02]; girls: B = −0.17, 95% CI [−0.29, −0.04]) and time spent by teachers in management tasks (boys: B = −0.42, 95% CI [−0.70, −0.15]; girls: B = −0.46, 95% CI [−0.63, −0.28]) were negatively associated to PACER. Discussion/Conclusion: Promoting CRF in PE can be achieved by providing active class contexts, such as gameplay, reducing management time, and promoting in-class and out-of-class fitness. © 2023 Human Kinetics, Inc.